Категориальная оппозиция предельность/ непредельность в русском и польском языках - Dyusekeneva, Indira; Kilevaya, Ludmila (Acta Polono-Ruthenica, 2018)
The article investigates grammatical means with the help of which the categorical opposition of telicity/ atelicity is expressed in the Russian and Polish languages with the projection on the mental characteristics of their speakers. Grammatical category of aspect is put in the center of the investigation, with the help of which the internal time as qualitative characteristics of action performance is expressed, as against to the external time which is expressed by grammatical meanings of the category of verb tense. It is asserted that the prevalence of telic verbs in speech practice of the Russian and Polish languages proves the importance of the quality of an action, bringing an action to possible endpoint for the Slavic people.